2022
DOI: 10.3390/nu14245267
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Malnutrition in Hospitalized COVID-19 Patients: A Systematic Review and Meta-Analysis

Abstract: (1) Background: Studies have reported that COVID-19 may increase the risk of malnutrition among patients. However, the prevalence of such risk in hospitalized COVID-19 patients is uncertain due to the inconsistent use of assessment methods. (2) Methods: PubMed, Web of Science, and EMBASE were searched to identify studies on the nutritional status of hospitalized COVID-19 patients. A pooled prevalence of malnutrition risk evaluated by Nutrition Risk Score (NRS-2002) was obtained using a random effects model. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Although most participants return to their original weight after recovery [17], here we have shown that six months after discharge, the BMI is still lower than baseline, and that weight gain is associated with HGS improvement. It has been estimated that the prevalence of malnutrition among individuals hospitalised with COVID-19 ranges between 12% and 83% in general ward patients and 31% and 94% in patients admitted to the ICU [49]. An association between malnutrition and HGS has been reported in COVID-19 patients [29], prompting the need for nutritional interventions aimed at improving physical function in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Although most participants return to their original weight after recovery [17], here we have shown that six months after discharge, the BMI is still lower than baseline, and that weight gain is associated with HGS improvement. It has been estimated that the prevalence of malnutrition among individuals hospitalised with COVID-19 ranges between 12% and 83% in general ward patients and 31% and 94% in patients admitted to the ICU [49]. An association between malnutrition and HGS has been reported in COVID-19 patients [29], prompting the need for nutritional interventions aimed at improving physical function in this population.…”
Section: Discussionmentioning
confidence: 99%
“…En personas mayores, el ingreso hospitalario conlleva un conjunto de riesgos y consecuencias adversas. Durante una hospitalización, incluso breve, los pacientes mayores pueden enfrentar complicaciones como el delirium o el deterioro funcional, lo que puede impactar de manera significativa en su calidad de vida posterior 24,25 y en la necesidad de establecer nuevos recursos sociales 26 , el riesgo de adquirir desnutrición y la aparición de sarcopenia 27,28 .…”
Section: Falta De Sensibilizaciónunclassified
“…During self-isolation at home, people of low- and middle-income countries (LMICs) had a limited food intake, whereas people in developed countries increased their caloric intake, 192 particularly in terms of processed and cheaper food with a low nutritional value 193 Moreover, an increased risk of malnutrition was reported in hospitalized COVID 19 patients, regardless of country. 194…”
Section: Bone Damage Due To the Covid-19 Pandemicmentioning
confidence: 99%